Gender and Emotion An Interdisciplinary Perspective - Latu, Ioana; Kaiser, Susanne; Mast, Marianne Schmid (Peter Lang, 2013)
Women express more emotion than men, but do they also experience more emotion than men? Are emotions represented differently in men and women's brains? What are the origins of gender differences in emotions - are we born different or is it socialization that renders us different? What are the implications of gender differences in emotion for general well-being, insomnia, depression, antisocial behavior, and alexithymia? What are the most appropriate methodologies for the empirical study of gender differences in emotional experiences? In the current book, coordinated by The Swiss Center for Affective Sciences, these questions are answered by reviewing research on general emotional expression and experience, but also on specific emotions and affective experiences such as shame, empathy, and impulsivity. We propose an interdisciplinary contribution to the field of gender and emotions, with works authored by specialists in the fields of psychology, neuroscience, psychiatry, economics, philosophy, and anthropology.
Description based on print version record.
KU Select 2019: HSS Backlist Books
Keywords: Social Science / Women's Studies; Social sciences; Electronic books